Overviews of Biological Importance of Quercetin: A Bioactive Flavonoid - David, Alexander Victor Anand; Arulmoli, Radhakrishnan; Parasuraman, Subramani (Pharmacognosy Reviews)
Antioxidants are substances that may protect cells from the damage caused by unstable molecules such as free radicals. Flavonoids are phenolic substances widely found in fruits and vegetables. The previous studies showed that the ingestion of flavonoids reduces the risk of cardiovascular diseases, metabolic disorders, and certain types of cancer. These effects are due to the physiological activity of flavonoids in the reduction of oxidative stress, inhibiting low‑density lipoproteins oxidation and platelet aggregation, and acting as vasodilators in blood vessels. Free radicals are constantly generated resulting in extensive damage to tissues leading to various disease conditions such as cancer, Alzheimer’s, renal diseases, cardiac abnormalities, etc., Medicinal plants with antioxidant properties play a vital functions in exhibiting beneficial effects and employed as an alternative source of medicine to mitigate the disease associated with oxidative stress. Flavonoids have existed over one billion years and possess wide spectrum of biological activities that might be able to influence processes which are dysregulated in a disease. Quercetin, a plant pigment is a potent antioxidant flavonoid and more specifically a flavonol, found mostly in onions, grapes, berries, cherries, broccoli, and citrus fruits. It is a versatile antioxidant known to possess protective abilities against tissue injury induced by various drug toxicities.
Keywords: Antioxidant; bioflavonoid; free radical; quercetin